Strong-coupling theory of high-temperature superconductivity - Alexandrov, A. S. (Cambridge : Cambridge University Press, 2013)
High-temperature superconductivity has transformed solid state science, however there is no single accepted theory to explain its origin. This book introduces the strong-coupling or bipolaron theory and is aimed at researchers and academics. It provides a thorough and balanced overview of the theory, discussing experimental observations, applications and alternative theories --
Includes bibliographical references (pages 158-178) and index.
Keywords: High temperature superconductivity; Coupling constants